PENGARUH DOSIS PUPUK KASCING DAN NITROGEN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA (LACTVCA SATIVA L.) VAR GEORGIA - Winten, Ketut Turaini Indra (AGRICA, 2008)
The low of growth and yield of lettuce is quite often caused by the low of soil fertility, especially nitrogen and C-organic content. Poor soil physical properties also contribute to the cause of low yield of lettuce. Improved soil physical and chemical properties by adding casting fertilizers and nitrogen are expected to be able to increase the yields of lettuce. The field experiment was conducted in Candikuning village, district of Baturiti, Tabanan regency, from October 2005 to January 2006. The objective of the experiment was to study the effect of casting fertilizer and nitrogen rates on the growth and yields of lettuce. A randomized complete block design was used in this experiment and two treatment factors were imposed. Those two treatment factors were rates of casting fertilizers (i.e. 0, 10, 20 and 30 t ha"1 ) and rates of N (i.e. 0, 92, 138 and 184 kg N ha"1), which were arranged factorially and repeated three times. Results of the experiment indicated that interaction between casting fertilizer and nitrogen rates did not significantly affect the yields of lettuce. The rates of N only significantly affected several growth variables and the oven-dry weight of heads plant-1. Increased rates of N from 0 to 92 kg N ha-1 significantly resulted in the oven-dry weight of heads of 2.798 g plant-1 which was 13.9% higher than that of 0 kg N ha-1. Rates of casting fertilizer significantly affected head diameter and the oven-dry weight of heads plant"1 and ha-1. Increased rates of casting fertilizer from 0 to 10 t ha-1 gave the oven-dry weight of heads as much as 0.232 t ha"1 or 9.43% higher than the weight given by the rate of 0 t ha-1. The effects of rates of casting fertilizer and N were only significant on several soil physical properties. The relationship between rates of casting fertilizer and yields of lettuce was quadratic (Y = 0.21135 + 0.0032 X - 0.001 X2 ; R2 = 0.981). The optimum rate of casting fertilizer was 16.0 t ha-1 with the maximum oven-dry weight of heads of 0.237 t ha-1, meanwhile, the optimum rate of N had not obtained in this experiment.